Cycling across Political Science Research. Issue 4 (28th December 2016) - Hibbing, John R.
Abstract : I extensively agree with Lieberman's main argument and especially with his recommendations to graduate students and journal editors, which come at a critical time for our discipline's development and future relevance. However, I depart from Lieberman on two issues. First, I argue that the research cycle is circular, and not teleological as Lieberman implies. For instance, randomized control trial (RCT) studies could be the start (and not the end) of a research cycle that leads to more descriptive and qualitative analysis in order to improve our understanding of causality. Second, I believe that the size of effects in RCT studies does matter, among other reasons because small effects might be symptoms of defective conceptualization of the main research problem.